Peran Guru Sosiologi Menyiapkan Kemampuan Berpikir Kritis Siswa dalam Proses Pembelajaran Sosiologi Siswa di SMA N 2 Sipora - Siti Ramadah Yanti N; Nurlizawati Nurlizawati (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the low critical thinking ability of students in learning in accordance with the indicators of critical thinking skills assessment in learning. Related to the low critical thinking ability of students in learning, the importance of the role of a teacher to prepare students' critical thinking skills in learning. The teacher is the most important component in learning activities that can interact directly with students. Teachers have an important role to form quality students. The purpose of this study was to analyze the role of sociology teachers in preparing students' critical thinking skills in the sociology learning process at SMA N 2 Sipora. This study uses a qualitative approach. The informant selection technique is purposive sampling, which is based on the researcher's criteria. The data was collected by interviewing 3 sociology teachers at SMA N 2 Sipora, 3 students in class X IPS 1 and the Curriculum Representative of SMA N 2 Sipora, then observing the sociology learning activities and the latest data was documentation in the form of photos, lesson plans documents and so on. In this study using data analysis from Miles and Huberman, namely data reduction, data presentation, and data verification. The theory used in the research on the role of the teacher in preparing students' critical thinking skills in the sociology learning process at SMA N 2 Sipora is constructivism theory. The results of this study are the first role of the sociology teacher as class manager, in the form of creating an atmosphere of fun learning activities, attracting students' attention and managing learning. Second, the role of sociology teachers as facilitators, designing learning media and innovative learning models. Third, the role of the sociology teacher as a motivator, providing direction, advice, and approaching. Fourth, the teacher's role as a demonstrator, the existence of performances and mastery of the material in advance or self-preparation.